2013
DOI: 10.1016/j.chembiol.2013.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Free Glycine Accelerates the Autoproteolytic Activation of Human Asparaginase

Abstract: Human asparaginase 3 (hASNase3), which belongs to the N-terminal nucleophile (Ntn) hydrolase superfamily, is synthesized as a single polypeptide that is devoid of asparaginase activity. Intramolecular autoproteolytic processing releases the amino group of Thr168, a moiety required for catalyzing asparagine hydrolysis. Recombinant hASNase3 purifies as the uncleaved, asparaginase-inactive form, and undergoes self-cleavage to the active form at a very slow rate. Here we show that the free amino acid glycine selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 31 publications
3
58
2
Order By: Relevance
“…An SDS–PAGE gel was run to establish the identity of the protein with a T M of 65 °C, and as previously observed and reported, we found three bands wherein 50% of the sample is a 33 kDa species corresponding to uncut protein and 50% of the sample is comprised of 18 and 15 kDa species that correspond to the α and β subunits of hASRGL1 after processing. 1,5 We noted that the d F /d T (change in fluorescence/change in temperature) curves from this experiment were asymmetrical in appearance; thus, to gain further insight, we fit the area under the d F /d T curves by summation of multiple Gaussian equations (MagicPlot Student, Magicplot Systems LLC). As shown in Figure 2A, at time 0 h, the d F /d T area is well fitted to three Gaussian curves with the main peak at 61 °C and two shoulders at 56 and 65 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An SDS–PAGE gel was run to establish the identity of the protein with a T M of 65 °C, and as previously observed and reported, we found three bands wherein 50% of the sample is a 33 kDa species corresponding to uncut protein and 50% of the sample is comprised of 18 and 15 kDa species that correspond to the α and β subunits of hASRGL1 after processing. 1,5 We noted that the d F /d T (change in fluorescence/change in temperature) curves from this experiment were asymmetrical in appearance; thus, to gain further insight, we fit the area under the d F /d T curves by summation of multiple Gaussian equations (MagicPlot Student, Magicplot Systems LLC). As shown in Figure 2A, at time 0 h, the d F /d T area is well fitted to three Gaussian curves with the main peak at 61 °C and two shoulders at 56 and 65 °C.…”
Section: Resultsmentioning
confidence: 99%
“…One method yielding fully active enzyme involves the bicistronic co-expression of the separate α and β subunits, with the main disadvantage being very low yields of properly assembled protein. 4 The finding that free glycine (Gly) accelerates and facilitates full intramolecular cleavage of wt-hASRGL1 was another significant advance, 5 although mutational studies of active site residues have shown that glycine does not always facilitate autoprocessing, rendering kinetic quantitation difficult or impossible in certain cases. 3 Our group also previously solved this issue by creating a fully activated version of hASRGL1 by means of a circular permutation (cp-hASRGL1).…”
mentioning
confidence: 99%
“…We would like to emphasize that the distinct enzymatic activities assigned to rat and human 60-kDa lysophospholipases warrant further analyses at the cellular level to elucidate the physiological role of these two-domain proteins. Our studies on L-asparaginase activity inherent to the N-terminal domain of this 60-kDa protein expands the basis of our work aiming at the identification and molecular engineering of enzymes of human origin (10,21) that might become suitable for replacing bacterial enzymes as approved therapeutics in the treatment of leukemias.…”
Section: Tablementioning
confidence: 95%
“…Subsequently, aliquots were tested for residual L-asparaginase activity by the Nesslerization method (29 main protein has been only poorly characterized in one report (24). Our primary motivation to produce and functionally characterize the N-terminal domain of this protein, which structurally and according to its catalytic in vitro properties significantly resembles E. coli cytoplasmic L-asparaginase (ansA; EcASNase1), originated from our previous work on human enzymes that possess L-asparaginase activity (10,19,21). The discovery, molecular engineering, and in vitro evolution of catalytically efficient human L-asparaginases are thought to lay the basis for the replacement of bacterial L-asparaginases presently used as antileukemia therapeutics despite adverse side effects mainly attributed to their bacterial origins (54).…”
Section: Tablementioning
confidence: 99%
“…59 We are presently probing the general applicability of our experimental strategy to more sensitive biomacromolecules such as various enzymes of human origin. Notably, we embarked on encapsulation of a human L-asparaginase that we recently characterized structurally and functionally 60 and that could replace enzymes of nonhuman origin. …”
Section: ■ Conclusionmentioning
confidence: 99%